Appunti su percezione delirante e teoria della nascita - Bisconti, Paola (Il sogno della farfalla, 2019)
In this article the author analyzes the concept of delusional perception according to the Human Birth Theory formulated by the psychiatrist Massimo Fagioli. Delusional perception is a key element in order to comprehend and cure psychosis. Contrary to Matussek and Conrad, Fagioli claims that this symptom is not related to any perceptive disorder but instead it should be considered as a thought disorder. In particular Fagioli affirms that the cause should be identified in human relationships when the mentally ill loses the “capability to imagine”. Therefore the patient becomes unable to see, sense and think for a lack of affection of the non-conscious thought.